Serum microRNAs as novel biomarkers for primary sclerosing cholangitis and cholangiocarcinoma. (17th May 2016) - Bernuzzi, F.; Marabita, F.; Lleo, A.; Carbone, M.; Mirolo, M.; Marzioni, M.; Alpini, G.; Alvaro, D.; Boberg, K. M.; Locati, M.; Torzilli, G.; Rimassa, L.; et al.
Summary: The diagnosis of primary sclerosing cholangitis (PSC) is difficult due to the lack of sensitive and specific biomarkers, as is the early diagnosis of cholangiocarcinoma (CC), a complication of PSC. The aim of this study was to identify specific serum miRNAs as diagnostic biomarkers for PSC and CC. The levels of 667 miRNAs were evaluated in 90 human serum samples (30 PSC, 30 CC and 30 control subjects) to identify disease‐associated candidate miRNAs (discovery phase). The deregulated miRNAs were validated in an independent cohort of 140 samples [40 PSC, 40 CC, 20 primary biliary cirrhosis (PBC) and 40 controls]. Receiver operating characteristic (ROC) curves were established and only miRNAs with an area under the curve (AUC) > 0·70 were considered useful as biomarkers. In the discovery phase we identified the following: 21 miRNAs expressed differentially in PSC, 33 in CC and 26 in both in comparison to control subjects as well as 24 miRNAs expressed differentially between PSC and CC. After the validation phase, miR‐200c was found to be expressed differentially in PSC versus controls, whereas miR‐483‐5p and miR‐194 showed deregulated expression in CC compared with controls. We also demonstrate a difference in the expression of miR‐222 and miR‐483‐5p in CC versus PSC. Combination of these specific miRNAs further improved the specificity and accuracy of diagnosis. This study provides a basis for the use of miRNAs as biomarkers for the diagnosis of PSC and CC.